Hardware Validation of the Advanced Plant Habitat on ISS: Canopy Photosynthesis in Reduced Gravity - Monje, Oscar; Richards, Jeffrey T.; Carver, John A.; Dimapilis, Dinah I.; Levine, Howard G.; Dufour, Nicole F.; Onate, Bryan G. (Frontiers in Plant Science, 2020)
The Advanced Plant Habitat (APH) is the largest research plant growth facility deployed on the International Space Station (ISS). APH is a fully enclosed, closed-loop plant life support system with an environmentally controlled growth chamber designed for conducting both fundamental and applied plant research during experiments extending as long as 135 days. APH was delivered to the ISS in parts aboard two commercial resupply missions: OA-7 in April 2017 and SpaceX-11 in June 2017, and was assembled and installed in the Japanese Experiment Module Kibo in November 2018. We report here on a 7-week-long hardware validation test that utilized a root module planted with both Arabidopsis (cv. Col 0) and wheat (cv. Apogee) plants. The validation test examined the APH’s ability to control light intensity, spectral quality, humidity, CO2 concentration, photoperiod, temperature, and root zone moisture using commanding from ground facilities at the Kennedy Space Center (KSC). The test also demonstrated the execution of programmed experiment profiles that scheduled: 1) changes in environmental combinations (e.g. a daily photoperiod at constant relative humidity), 2) predetermined photographic events using the three APH cameras (overhead, sideview, and sideview near-infrared (NIR)), and 3) execution of experimental sequences during the life cycle of a crop (e.g., measure photosynthetic CO2 drawdown experiments). Arabidopsis and wheat were grown in microgravity to demonstrate crew procedures, planting protocols and watering schemes within APH. The ability of APH to contain plant debris was assessed during the harvest of mature Arabidopsis plants. Wheat provided a large evaporative load that tested root zone moisture control and the recovery of transpired water by condensation. The wheat canopy was also used to validate the ability of APH to measure gas exchange of plants from non-invasive gas exchange measurements (i.e. canopy photosynthesis and respiration). These features were evaluated by executing experiment profiles that utilized the CO2 drawdown technique to measure daily rates of canopy photosynthesis and dark-period CO2 increase for respiration. This hardware validation test confirmed that APH can measure fundamental plant responses to spaceflight conditions.